THE ROLE OF SCOUTING EXTRACURRICULAR ACTIVITIES IN RECOGNIZING SCOUTING SYMBOLS AT SCHOOL - Izhar Maulana; Nurul Khairunnisa; Dini Maulidia Putri Lubis (Journal of Quality Islamic Education Research, 2024)
The type of research used in this research is qualitative research. The data collection techniques carried out in this research are as follows: (1) Observation (Observation, documentation and traiangulation. Research results. The introduction of the Scout symbol through extracurricular activities at school is a learning activity that is held outside of hours. lessons tailored to their needs, starting from their potential, talents and interests through activities specifically organized by students. Extracurricular activities are learning activities carried out outside face-to-face class hours, carried out at school or outside school to broaden horizons or abilities that have been learned from various subjects, activities carried out outside of normal hours can be carried out outside of school hours in order to broaden the relationship between lessons and also channel the talents of students' interests and complete human development as a whole.